Application of the discovery learning model to improve students' critical thinking skills in Pancasila education for grade VII.B at Al-Irsyad Islamic Junior High School in Sidenreng Rappang Regency - Heril Heril; Lila Ramdika Rahim (Privietlab, 2025)
This study aims to describe the implementation of the Discovery Learning model on the critical thinking skills of students in class VII.B at Al-Irsyad Islamic Junior High School in Sidenreng Rappang Regency in the subject of Pancasila Education. Classroom Action Research (CAR) was used, consisting of two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. Before the first and second cycles were conducted, a pre-cycle was carried out to obtain initial information and identify problems in the classroom. The results of the research showed that in the pre-cycle, 50% of the predetermined indicators were found. However, after the first cycle and using the Discovery Learning model in Pancasila Education, there was an increase of 15% to 65%. In the second cycle, there was an increase from 65% to 80%. The results showed that there were significant improvements in critical thinking skills after the implementation of Discovery Learning in class VII.B at Al-Irsyad Islamic Junior High School in Sidenreng Rappang Regency.